2021
DOI: 10.3390/su13020495
|View full text |Cite
|
Sign up to set email alerts
|

Web Communication: A Content Analysis of Green Hosting Companies

Abstract: While many studies in the field of environmental communication have focused on exploring the environmental impact of social media, this research paper takes a different turn. It investigates, through a qualitative content analysis, 391 websites that support and provide green hosting services. This study is considered the first in the field that aims to examine in-depth how these green websites tend to communicate their green services. Therefore, its contribution is to enhance the relevant bibliography and pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 41 publications
(63 reference statements)
0
7
0
3
Order By: Relevance
“…The research design involves content analysis of service measures presented by OCPs on their websites. The content analysis method is a qualitative research method that can be used for analyzing all kinds of media texts [54]. It is considered a common method in communication studies and has been used widely in investigating communication phenomena based mostly on texts on websites [54][55][56].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The research design involves content analysis of service measures presented by OCPs on their websites. The content analysis method is a qualitative research method that can be used for analyzing all kinds of media texts [54]. It is considered a common method in communication studies and has been used widely in investigating communication phenomena based mostly on texts on websites [54][55][56].…”
Section: Methodsmentioning
confidence: 99%
“…The content analysis method is a qualitative research method that can be used for analyzing all kinds of media texts [54]. It is considered a common method in communication studies and has been used widely in investigating communication phenomena based mostly on texts on websites [54][55][56]. Application of content analysis began with actual observations and the collection of original documents, and then proceeded to analyze, code, and refine the concepts and categories before constructing the systematic theory [57,58].…”
Section: Methodsmentioning
confidence: 99%
“…Ταυτόχρονα η περιβαλλοντική επικοινωνία σύμφωνα με τον Harrison (1993), είναι η αμφίδρομη ανταλλαγή πληροφοριών και αφορά στο περιβάλλον. Σύμφωνα με τους Karyotakis and Antonopoulos (2021), η περιβαλλοντική επικοινωνία αρχικά ήταν ένας περιορισμένος όρος καθώς δεν σχετιζόταν με όλα αυτά τα κομμάτια της επικοινωνίας που περιλαμβάνει σήμερα. Την ίδια στιγμή, τα ΜΜΕ σύμφωνα με τους Friedman and Friedman (1988), θα πρέπει να μην μεταδίδουν απλώς πληροφορίες για περιβαλλοντικά θέματα αλλά να παρουσιάζουν στον κόσμο την πραγματική κοινωνική, οικονομική και οικολογική πλευρά των προβλημάτων που σχετίζονται με το περιβάλλον ενώ ταυτόχρονα θα πρέπει να δίνουν πιθανές λύσεις (Bednarek and Caple, 2010).…”
Section: εισαγωγήunclassified
“…In addition, authors Do Paco et al [18] highlight that green marketing is "the integral management process responsible for identifying, anticipating and satisfying the needs of customers and society in a profitable and sustainable manner". Therefore, green marketing does not only include those actions or strategies of organizations that increase the quality of life of the population, taking into account its satisfaction of their needs and wishes but also as an increase in the quality of the environment where they are located [19].…”
Section: Green Marketingmentioning
confidence: 99%
“…Moreover, Foris et al [28] analyzed the environmental practices that hotels carry out on booking websites and how customers perceive them. The results indicated that the hotel sector needs to provide more information on environmental practices and better use different communication tools [19].…”
mentioning
confidence: 99%